Investigation of the broadband microwave absorption of citric acid coated Fe3O4/PVDF composite using finite element method - Adebayo, L.L. (MDPI AG, 2019)
Magnetite (Fe3O4) have been thoroughly investigated as microwave absorbing material due to its excellent electromagnetic properties (permittivity and permeability) and favorable saturation magnetization. However, large density and impedance mismatch are some of the limiting factors that hinder its microwave absorption performance (MAP). Herein, Fe3O4 nanoparticles prepared by facile co-precipitation method have been coated with citric acid and embedded in a polyvinylidene fluoride (PVDF) matrix. The coated Fe3O4 nanoparticles were characterized by X-ray diffraction spectrometer (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), and vibrating sample magnetometer (VSM). COMSOL Multiphysics based on the finite element method was used to simulate the rectangular waveguide at X-band and Ku-band frequency range in three-dimensional geometry. The citric acid coated Fe3O4/PVDF composite with 40 wt. filler loading displayed good microwave absorption ability over the studied frequency range (8.2-18 GHz). A minimum reflection loss of -47.3 dB occurs at 17.9 GHz with 2.5 mm absorber thickness. The composite of citric acid coated Fe3O4 and PVDF was thus verified as a potential absorptive material with improved MAP. These enhanced absorption coefficients can be ascribed to favorable impedance match and moderate attenuation. Â© 2019 by the authors.